Identification of Ideal Trial Sites and Wide Adaptable T. Aus Rice Genotypes Suitable for Bangladesh - Khatun, M; Ahmed, MME; Syed, MA; Akter, F; Das, S; Haq, ME; Dipti, SS (Bangladesh Rice Journal, 2020)
GGE biplot study is an effective tool for many crops including rice to identify mega-environments, ideal trial site and suitable genotypes for general and specific adaptation. An attempt was made to find promising T. Aus rice genotypes having suitable grain quality, better agronomic parameters and ideal test location for T. Aus rice growing areas. In this study, a total of 11 promising genotypes along with two popular cultivars BR26 and BRRI dhan48 were tested across six locations; Cumilla, Gazipur, Rajshahi, Rangpur in T. Aus 2016 and 2017 whereas Habiganj and Kushtia only in T. Aus 2017 season. From GGE biplot study, BRRI RS, Rajshahi (E8) was the most discriminating and ideal location for evaluating T. Aus rice genotypes in Bangladesh condition while BRRI RS, Cumilla 2016 (E1) showed the least discriminating ability and the least representative location. From two years combination data, BR9011-19-1-2 (G6) recorded the highest average grain yield (5.11±0.68 t ha-1) but BR9011-46-2-2 (G2) was the most stable genotype having grain yield (4.97±0.62 t ha-1) and other stable genotypes with above average yield were BR9011-67-4-1 (G5), BR9011-34-3-2 (G1), BRRI dhan48 (G13), BR9039-28-3-2 (G9) and BR9039-9-1-3 (G8) indicated that these genotypes adapted to favourable environments. BR26 (G12) was found highly variable and less stable across the test environments. In addition, agronomic trait (plant height, growth duration) and grain quality traits were also considered for suitability and wider adaptation in T. Aus growing areas in Bangladesh. BR9011-46-2-2 (G2) and BR9011-19-1-2 (G6) were the better genotypes in most of the locations but, considering all of the parameters, the newly developed rice breeding line BR9011-67-4-1 (G5) has been identified as suitable genotype to release as a new variety for sustainable T. Aus rice production in Bangladesh. Bangladesh Rice j. 2019, 23(2): 77-85